Evaluation of Tall Fescue Cultivars - J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2016)
Spring 2015 yield was higher for ‘Ky 31 EF’ than for nine of the 19 other entries. Summer production of ‘PBU-B7’ was greater than for five lower-yielding entries. Total 2015 production was greater for ‘PBU-B1’ and Ky 31 EF than for seven other cultivars.
Keywords: pastures; tall fescue